Remote Sensing Applications in Fruit Crops: A Review - Devi Darshan; Purabi Tamuli Phukan; Vishal Gulab Vairagar; Sandeep Bhardwaj; Khan Chand; Nisha Boora; Surender Kumar; Subhash Verma (Archives of Current Research International, 2025)
Horticulture has become a significant agricultural venture in accelerating economic growth. Its contribution to a nation’s food security, nutritional well-being, and poverty reduction and employment opportunities is pivotal. Among its various facets, fruit crops hold a prominent position, comprising a significance share of horticultural production. However, the cultivation of fruit crops demands considerable capital investment and labor input. Embracing modern technologies for fruit orchard advancement and maximizing production potential is thus deemed essential. In today’s age, remote sensing emerges as a modern solution, providing efficient technology for managing crops in specific locations. Remote sensing, or RS, serves as a potent instrument facilitating the gathering and refreshing of data to formulate precise management strategies. Through the acquisition of electromagnetic data and imagery, RS enables straightforward manipulation via computer systems. Remote sensing has the potential to mitigate risks and limit harm, proving especially valuable for tailored management and precise agricultural practices, such as identifying crops, estimating areas, managing soil and nutrients, gauging biomass and yields, and evaluating damage caused by both living organisms and environmental factors. RS offers multifaceted benefits, including risk reduction, damage minimization and increased land productivity, thereby contributing to employment generation, enhanced exports and improved economic conditions, while also ensuring food and nutritional security.